Cell Death, Inflammation and Oxidative Stress in Neurodegenerative Diseases Mechanisms and Cytoprotective Molecules - Vejux, Anne (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Neurogenerative diseases encompass very different pathologies, which can be demyelinating or nondemyelinating, but which have common mechanisms such as cell death, oxidative stress and inflammation. A better understanding of these mechanisms allows the search for biomarkers and targets for new therapies. This special issue brings together different data on Alzheimer's disease, Parkinson's disease, and multiple sclerosis, detailing the mechanisms of cell death (necroptosis, ferroptosis), oxidative stress and inflammation but also the possibilities of neuroprotection via 5 research articles and 6 review articles. The different reviews allow us to take stock of cell death, oxidative stress and neuroinflammation in the context of neurodegenerative diseases but also in relation to other pathologies where these processes are involved.